Anglo-Western international school teachers as global middle class: portraits of three families. Issue 5 (3rd September 2019) - Tarc, Paul; Mishra Tarc, Aparna; Wu, Xi
ABSTRACT: This exploratory study on the global middle class (GMC) examines three representative experiences of the tens of thousands of Anglo-Western international schoolteachers (ISTs), who teach in private, K-12, English-immersion international schools for extended periods of time. The notion of GMC provokes consideration of social class making and forms of belonging of professional and managerial service workers who are 'middling actors' in the flows of transnational migration. We ground our analysis by examining three IST families as a unique group within the GMC. We find that ISTs, oriented by pre-sojourn middle-class histories, differentially (re)fashion their social class locations in the more elite transnational milieu of the international schools. These families accumulate and exchange economic, cultural and social capital under their transnational routes, connections and returns. Their children's access to an elite international education as a condition of their international employment represents a unique form of school choice.